2010
DOI: 10.1152/ajpcell.00015.2010
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 hemichannels mediate the Ca2+ influx induced by extracellular alkalinization

Abstract: Although alkaline pH is known to trigger Ca(2+) influx in diverse cells, no pH-sensitive Ca(2+) channel has been identified. Here, we report that extracellular alkalinization induces opening of connexin 43 hemichannels (Cx43 HCs). Increasing extracellular pH from 7.4 to 8.5, in the presence of physiological Ca(2+)/Mg(2+) concentrations, rapidly increased the ethidium uptake rate and open probability of HCs in Cx43 and Cx43EGFP HeLa transfectants (HeLa-Cx3 and HeLa-Cx43EGFP, respectively) but not in parental He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 76 publications
7
125
0
1
Order By: Relevance
“…For this, it is essential to use a purified and reconstituted preparation of HCs where there is no possibility of Ca 2ϩ transport through parallel unidentified pathways. Our results support previous interpretations that suggested a role of Ca 2ϩ fluxes through GJCs and HCs in physiological and pathophysiological conditions (17,21,(25)(26)(27)(28). Ca 2ϩ permeability is relatively high, similar to that for Na ϩ .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For this, it is essential to use a purified and reconstituted preparation of HCs where there is no possibility of Ca 2ϩ transport through parallel unidentified pathways. Our results support previous interpretations that suggested a role of Ca 2ϩ fluxes through GJCs and HCs in physiological and pathophysiological conditions (17,21,(25)(26)(27)(28). Ca 2ϩ permeability is relatively high, similar to that for Na ϩ .…”
Section: Discussionsupporting
confidence: 91%
“…Although most cells have fewer HCs than GJCs at the plasma membrane, the much higher extracellular [Ca 2ϩ ] suggests that HCs can have a significant role in Ca 2ϩ influx, at least under certain circumstances (17,21,(25)(26)(27)(28) or in disease-causing mutants that display higher Ca 2ϩ permeability (G45E mutant associated with keratitis ichthyosis deafness syndrome) (29). In summary, our results showed that Cx26 HCs are permeable to Ca 2ϩ and suggest that HCs can be a pathway for Ca 2ϩ influx into cells under conditions such as ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that hemichannels can be opened by various messengers and conditions, thereby providing a conduit that allows the passage of ions and molecules with MW up to 1.5 kDa. Hemichannels are permeable to Ca 2þ and may thus contribute to cellular Ca 2þ entry 4 and diffusive ATP release. 5 Moreover, hemichannel opening is [Ca 2þ ] i -dependent in a bimodal manner, [6][7][8][9][10] with moderate [Ca 2þ ] i elevation favouring opening and above $500 nM [Ca 2þ ] i inhibiting opening.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cx26, Cx32 and Cx43 HCs are permeable to Ca 2+ [73][74][75][76] and might be involved in initiation of intracellular rise in Ca 2+ signals. In protozoan infections, a key process in early stages of invasion is the rise in cytosolic Ca 2+ concentration [77].…”
Section: Intracellular Ca 2+ Mobilizationmentioning
confidence: 99%